Influence of corn processing provided in the diet on the ruminal dynamics of dairy steer - Vargas Junior, Fernando Miranda de; Sanchez, Luis Maria Bonnecarrère; Wechsler, Francisco Stefano [UNESP]; Bianchini, Waldmaryan [UNESP]; Oliveira, Marcus Vinicius Morais de; Schmidt, Patrick (Sociedade Brasileira de Zootecnia, 2011)
Objetivou-se com este trabalho avaliar a dinâmica ruminal de novilhos leiteiros recebendo dietas contendo grão de milho inteiro, milho moído na forma de quirera ou milho inteiro tratado com ureia. Para isso, foram mantidos em regime de confinamento seis animais fistulados no rúmen alimentados com dietas com teores semelhantes de energia e proteína. A dieta foi formulada com relação volumoso:concentrado de 40:60 na matéria seca e continha silagem de sorgo como volumoso. O delineamento utilizado foi na forma de um quadrado latino 3 × 3, com três animais e três períodos, e foi repetido duas ou quatro vezes conforme o parâmetro estudado, totalizando seis ou 12 repetições por dieta. O tratamento do grão de milho não influenciou o pH do líquido ruminal nem a degradabilidade ruminal da matéria seca, fibra em detergente ácido e celulose. Todas as dietas propiciaram concentração de N-amoniacal adequada para o crescimento microbiano ruminal; todavia, nos animais alimentados com grão de milho inteiro tratado com ureia, essa concentração foi significativamente menor. A atividade bacteriana é menor em animais alimentados com dietas contendo milho moído e não difere entre os animais alimentados com grão de milho inteiro ou grão de milho inteiro tratado com ureia.

The objective of the present study was to evaluate the ruminal dynamics of dairy steer fed diets containing whole corn grains, grains ground into grits or whole grain treated with urea. Thus, six rumen-fistulated animals were kept in confinement and fed diets with similar contents of energy and protein. The diet was formulated with 40:60 roughage:concentrate ratio in the dry matter using sorghum silage as roughage. The experiments followed a 3 × 3 latin square design, with three animals and three periods and they were repeated eith-er two or four times depending on the studied parameter, totaling six or 12 replicates per diet. Corn grain treatment did not affect the pH of the ruminal fluid neither the ruminal degradability of dry matter, acid detergent fiber and cellulose. All diets provided a concentration of amoniacal nitrogen suitable for ruminal microbial growth; however, for animals fed whole corn grain treated with urea, this concentration was significantly lower. Bacterial activity was lower in animals fed diets containing ground corn and they do not differ among animals fed whole corn grain or corn grains treated with urea.
Influência do processamento do milho fornecido na dieta na dinâmica ruminal de novilhos leiteiros
Keywords: atividade bacteriana; bovinos; degradabilidade in situ; bacterial activity; bovine; in situ degradability